MAKING BIOETHANOL TECHNIQUE MADE FROM OIL EMPTY FRUIT TUBES IN TREATMENT OF YEAR FERMENTATION AND YEAR DOSAGE WITH HEAT TEMPERATURE COMPRESSION OF 220 OC METHOD - Purnomo, Julian; irianto, irianto (Jurnal Pertanian, 2020)
Nowadays, biofuels are increasingly developed in the form of bioethanol which is gained from cassava. As the time passes by, however, this solution raises another issue as the excessive use of biofuels may create a competition between the needs for fuel and food. Waste empty bunch of palm oil (WEBP) constitutes as a cellulose material which is quite potential to be developed as raw materials for ethanol. So far, the WEBP is available in large quantities and it seems that the WEBP remains underused. In fact, it contains a high concentration of cellulose (45%). For that reason, this research attempted to gather an optimal formula of yeast dosage and the length of fermentation in order to produce standardized and high quality ethanol. The quality standards covered ethanol level (SNI17390:2008), methanol level (SNI7390:2008), acidity as CH3COOH (SNI7390:2008), pHe (SNI7390:2008, and appearance (visual observation) (SNI7390:2008). Therefore, they could be used to suffice alternative energy needs which were renewable and environmentally friendly. In detail, the present research aimed at identifying 1) the effect of the fermentation length, 2) understanding the effect of added dosage of the yeast, and 3) identifying the interaction between the fermentation length treatment and the treatment of added dosage of yeast. Results of the discussion indicated that the length of fermentation treatment had a significant effect as the longer the fermentation, the higher the ethanol level value. In addition, the ethanol level tended to increase, the sugar level tended to decline, and the pH value seemed to fall.